2002
DOI: 10.1097/00125817-200209000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to aminoglycoside ototoxicity: How many are at risk?

Abstract: Purpose: To assess the occurrence of two mutations associated with susceptibility to aminoglycoside ototoxicity.Methods: Genetic analysis of anonymized, residual diagnostic specimens. Results: One occurrence of the A1555G mutation and seven occurrences of the 961delT ϩ C(n) nucleotide change were found. Two previously unreported sequence changes, T961G and 956 -960insC, were also found in six and five specimens, respectively. Conclusions: Genetic susceptibility to aminoglycoside ototoxicity may be more common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 27 publications
3
77
0
Order By: Relevance
“…The first of these sampled umbilical cord blood of 1,773 neonates, of which only one carried the mutation. 27 The second screened 25 neonates that had altered otoacoustic emissions tests, among which the mutation was not found. 28 Screening of 300 neonates in Argentina and in 712 normal-hearing subjects did not detect the A1555G mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these sampled umbilical cord blood of 1,773 neonates, of which only one carried the mutation. 27 The second screened 25 neonates that had altered otoacoustic emissions tests, among which the mutation was not found. 28 Screening of 300 neonates in Argentina and in 712 normal-hearing subjects did not detect the A1555G mutation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Although the number of cases in both groups was different from the number in some published studies, and although the mutation was not found in both groups (HLG and control groups), we were able to confirm the results of studies that also did not find the mutation in non-Asian or Arab ethnic groups. [24][25][26][27][28][29] There is a single study in Brazil reporting the findings of five families with hearing loss cases in which the prevalence of the mutation was 2% (4 cases). Only one of these positive cases was associated with an assumed aminoglycoside exposure; no mutation was found in the control group composed by black, white or Asian (Japanese or Chinese) ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether an inherited susceptibility (Tang et al, 2002) exists among the investigated hares, we also examined the matrilinear haplotypes of all tissue samples (n585). Fifteen different haplotypes were found, but there was neither a significant correlation between haplotype and development of antibodies nor between haplotype and harboring of EBHSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this gene cause aminoglycoside-induced and nonsyndromic SNHL, which may be due to the A1555G [23][24][25][26][27], C1494T [28], T1095C [34][35][36][37], A827G [40,41], and 961 mutations [30][31][32][33]. No deafness-associated mutations in the mitochondrial 16S rRNA gene have been detected.…”
Section: Mitochondrial Rrna Mutations and Nonsyndromic Hearing Lossmentioning
confidence: 99%
“…By now, several mutations including A1555G [23][24][25][26][27], C1494T [28], T1095C [34][35][36][37], A827G [40,41], and 961 mutation [30][31][32][33] in the mitochondrial 12S rRNA gene have been found to be associated with nonsyndromic hearing loss. Surprisingly, all of these mutations are sensitive to aminoglycosides as indicated by extensive clinical observations and functional studies [5,41,68].…”
Section: Mtdna Mutations and Aminoglycoside Ototoxicitymentioning
confidence: 99%